Improving Student Creativity Through Talking Stick Method in Indonesian Language Learning - Anggreni, Alviana Dwi (Prosiding University Research Colloquium, 2021)
Bahasa Indonesia learning is a compulsory lesson taught from elementary school to college. the purpose of this research is to find out how the influence of talking stick method in improving the creativity of Indonesian language learning. The method in the study was to use class actions on students’ creativity by using talking stick method. The object of this study was a grade 2 student at SD Jambewangi who numbered 25 students. The results showed that the application of talking stick learning model is able to improve the learning of Bahasa Indonesia, this can be seen in the table of student’s practicality research results. The method in the study was to use class actions on students’ creativity by using talking stick methods. The object of this study was a grade 2 student at SD Jambewangi who numbered 25 students. The results showed that the application of talking stick learning model is able to improve the learning of Bahasa Indonesia, this can be seen in the table of student’s practicality research results. The conclusion of this study is that talking stick learning method makes students more understanding in answering questions given in Bahasa Indonesia material. Therefore, with the application of talking stick learning methods can be developed to improve the learning process in the classroom and student learning outcomes.